2020
DOI: 10.1007/s10661-020-08302-5
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the risk level of physicochemical and bacteriological twin contaminants of water resources in part of the western Niger Delta region

Abstract: This study was carried out to assess the physicochemical and bacteriological contaminants of surface, shallow well and municipal borehole waters in part of the western Niger Delta as a way of safeguarding public health against waterborne diseases. A total of 72 water samples collected from the study area were analysed and their results show that the pH average value ranges from 6.2 in the dry to 8.5 in the rainy seasons for surface water, 6.6 and 8.3 for shallow well water and 6.5 to 8.4 for borehole water. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The samples S1KR and S2KR had an electrical conductivity of 140 and 160 µS/cm while S1OK and S4OK had 6.91 and 5.62 µS/cm. The results of the findings agreed with the earlier report of Ocheli et al (2020) whose study observed that ground water had a high level of electrical conductivity than other sources. Suggestions that EC values higher than 400 µS/cm definitely contains a number of ions and radicals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The samples S1KR and S2KR had an electrical conductivity of 140 and 160 µS/cm while S1OK and S4OK had 6.91 and 5.62 µS/cm. The results of the findings agreed with the earlier report of Ocheli et al (2020) whose study observed that ground water had a high level of electrical conductivity than other sources. Suggestions that EC values higher than 400 µS/cm definitely contains a number of ions and radicals.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the present study agrees strongly with the report of Igwe et al (2021) whose investigation obtained a range of values between 6.8 to 6.9 while the control samples had a range from 6.0 to 7.1. In a related study, Ocheli et al (2020) reported ranges between pH 6.2 and 8.5 for surface water, pH 6.6 and 8.3 for shallow well and pH 6.5 and 8.4 for borehole water while WHO permissible limit of 6.5-8.5. These concentration values agree with previously data in the Niger Delta Region (Bolaji and Tse, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, the south-south and south-west have abundant surface and groundwater, and annual rainfall is high. Specifically, the major sources of water in the south-south are creeks, rivers, shallow wells and boreholes; and studies of water quality in this part have been tailored to them ( Ihunwo et al., 2020 ; Ocheli et al., 2020 ; Owamah, 2020 ; Owoyemi et al., 2019 ). Similarly, studies in the south-west have been related to several rivers, lagoons, groundwaters, lake and stream, as these are abundant ( Ebele et al., 2020 ; Ezemonye et al., 2019 ; Gbadebo, 2020 ; Odukoya et al., 2017 ; Ogunbanwo et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, drinking water must comply with hygienic, chemical and even organoleptic quality standards (Fisher et al, 2020). When drinking water does not meet these quality standards, it can cause water-borne infections including cholera (Ocheli et al, 2020), bloody diarrhea (Antwi-Agyei et al, 2016), dysentery, hepatitis, typhoid fever and certain virus diseases (Ngure et al, 2019). While water-related diseases have largely been eliminated in developed countries, they remain one of the leading causes of death in developing countries, particularly in Africa (Soncy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Five million deaths per year are believed to be due to waterborne diseases, including two million deaths of children under five years of age (WHO, 2019a). Larger quantities of water and a reduction in the risk of contamination of the water consumed are two of the predominant elements for a better prevention of the faecal danger, which is the main cause of diarrhoeal diseases that constitute a real scourge in African cities (Ocheli et al, 2020;Toure et al, 2019). These problems are exacerbated in urban areas, due to a combination of aggravating factors: high density of unhealthy housing, lack of sanitation, pollution of unprotected water sources (Igbinosa and Aighewi, 2017).…”
Section: Introductionmentioning
confidence: 99%